PYŁAT, Joanna, 2012. Friends of Poland 1982–2009 - Chwastyk-Kowalczyk, Jolanta (Respectus Philologicus, 2012)
PYŁAT, Joanna, 2012. Friends of Poland 1982–2009. London: Polish Society of Arts and Sciences Abroad, ss. 133.
Keywords: none